The Endosomal–Lysosomal Pathway Is Dysregulated by APOE4 Expression in Vivo - Nuriel, Tal; Peng, Katherine Y.; Ashok, Archana; Dillman, Allissa A.; Figueroa, Helen Y.; Apuzzo, Justin; Ambat, Jayanth; Levy, Efrat; Cookson, Mark R.; Mathews, Paul M.; Duff, Karen E. (Frontiers in Neuroscience, 2017)
Possession of the ε4 allele of apolipoprotein E (APOE) is the major genetic risk factor for late-onset Alzheimer’s disease (AD). Although numerous hypotheses have been proposed, the precise cause of this increased AD risk is not yet known. In order to gain a more comprehensive understanding of APOE4's role in AD, we performed RNA-sequencing on an AD-vulnerable vs. an AD-resistant brain region from aged APOE targeted replacement mice. This transcriptomics analysis revealed a significant enrichment of genes involved in endosomal-lysosomal processing, suggesting an APOE4-specific endosomal-lysosomal pathway dysregulation in the brains of APOE4 mice. Further analysis revealed clear differences in the morphology of endosomal-lysosomal compartments, including an age-dependent increase in the number and size of early endosomes in APOE4 mice. These findings directly link the APOE4 genotype to endosomal-lysosomal dysregulation in an in vivo, AD pathology-free setting, which may play a causative role in the increased incidence of AD among APOE4 carriers.